2014
DOI: 10.1126/scitranslmed.3008095
|View full text |Cite
|
Sign up to set email alerts
|

Localized Oncolytic Virotherapy Overcomes Systemic Tumor Resistance to Immune Checkpoint Blockade Immunotherapy

Abstract: Preexisting lymphocytic infiltration of tumors is associated with superior prognostic outcomes in a variety of cancers. Recent studies also suggest that lymphocytic responses may identify patients more likely to benefit from therapies targeting immune checkpoints, suggesting that therapeutic efficacy of immune checkpoint blockade can be enhanced through strategies that induce tumor inflammation. To achieve this effect, here we explored the immunotherapeutic potential of oncolytic Newcastle Disease Virus (NDV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
589
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 618 publications
(613 citation statements)
references
References 40 publications
18
589
0
6
Order By: Relevance
“…The high correlation of viral defense signaling with mutational burden suggests that genetic changes, increases in ERVs, and viral defense genes could predict response to immune checkpoint and other immunomodulatory approaches. Finally, our drug approach to upregulate viral defense signaling might be compared to the use of oncolytic viruses to induce inflammatory immune infiltrates at tumor sites to sensitize to immunomodulation (Zamarin et al, 2014). methods at 1, 3, or 7 days following removal of drug.…”
Section: Discussionmentioning
confidence: 99%
“…The high correlation of viral defense signaling with mutational burden suggests that genetic changes, increases in ERVs, and viral defense genes could predict response to immune checkpoint and other immunomodulatory approaches. Finally, our drug approach to upregulate viral defense signaling might be compared to the use of oncolytic viruses to induce inflammatory immune infiltrates at tumor sites to sensitize to immunomodulation (Zamarin et al, 2014). methods at 1, 3, or 7 days following removal of drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, dramatic as they are, these remissions occur in a minority of the patients. A number of strategies are being developed to enhance the therapeutic effects of PD1/PD-L1 blockade, such as combining it with other anticancer therapies (13)(14)(15).…”
mentioning
confidence: 99%
“…Most interestingly, they found that NDV treatment not only had a local effect on the tumor to which it was injected, but also stimulated a systemic abscopal response; tumors at distant sites also shrunk. Specifically, the oncolytic NDVs induced immunogenic cell death of the injected tumor, eliciting tumor-specific effector T cells that could then seek out and destroy other tumors bearing those same antigens (24). Zamarin and colleagues found that distant tumors are efficiently infiltrated with activated effector T cells but not with Tregs.…”
Section: Increasing Immune Traffic Into Tumorsmentioning
confidence: 99%